Mitral Valve Regurgitation and Left Ventricular Dysfunction Treatment with an Intravalvular Spacer. Issue 1 (23rd October 2014) - Svensson, Lars G.; Ye, Jian; Piemonte, Thomas C.; Kirker‐Head, Carl; Leon, Martin B.; Webb, John G.
Abstract Attempts at transcatheter treatment of mitral valve regurgitation have generally been modeled on proven surgical procedures such as leaflet repair, annuloplasty, or prosthetic valve implantation. We introduce a novel approach to directly reducing the regurgitant orifice: the mitral valve spacer, a balloon that attempts to reduce the regurgitant orifice. doi: 10.1111/jocs.12453 (J Card Surg 2015;30:53–54)